City logistics: a case study from Minsk - Markava, Maryia; Chocholáč, Jan; Polák, Michal; Jirásková, Andrea (Kaunas University of Technology, 2019)
Worldwide, there is a steady increase in urban populations. Urban agglomerations are currently developing. This brings with it greater demands on ensuring high-quality transport services and on building new traffic communication. The most serious problems for urban residents are caused by the high intensity of road traffic. Road transport brings with it negative consequences (noise, vibration, exhalation, pollution of the atmosphere, etc.), which brings further problems and the associated decrease in the quality of life of the population. City Logistics is a way to improve the traffic situation in urban and metropolitan areas. Minsk is the capital, largest and industrial city of Belarus, located in the center of Belarus. Transport problems in Minsk are deteriorating the environment and lowering people's satisfaction and quality of life. Nowadays, there are about two million people living in Minsk, which brings with it many traffic complications. The aim of this article is to propose appropriate measures for the capital city of Belarus – Minsk based on an analysis of current approaches to city logistics.
City logistika: případová studie z Minsku
Keywords: city logistics; mobility; bike sharing; hub and spoke; public transport; city logistika; mobilita; sdílení kol; hub and spoke; veřejná doprava